Marlen Haushofer: Recollections of Crime and Complicity - Maria-Regina Kecht (Studies in 20th & 21st Century Literature, 2007)
This essay wants to introduce readers to one of Austria's most astute women writers of the immediate postwar period. Marlen Haushofer, in contrast to her contemporary Ingeborg Bachmann, has not (yet) gained international renown despite her literary craftsmanship. Looking at those works of her that most poignantly thematize the postwar reaction to the years of National Socialism and deal with the issues of guilt and responsibility, I focus on Haushofer's gendered perspective on the roles of victim, perpetrator, and bystander as played out in the seemingly apolitical microcosm of the family. The essay consists of an introductory discussion of the relevant political-historical context, a brief commentary on two thematically related short stories, and an analysis of the novella Wir töten Stella. In her scathing portrait of femininity in the patriarchal order of the fifties, Haushofer condemns women as accomplices in the perpetuation of corrupt structures and strategies of domination. She points to women's subordination and conspiracy of silence about evil-doing as powerful factors in the perpetuation of destruction. The metaphorical representation of Austrians' collective effort to forget their participation in Nazi crimes may be regarded as a gendered writing strategy allowing Haushofer to appear harmless and thus acceptable to her contemporaries.
Keywords: Austria; women writers; postwar; post-war; Marlen Haushofer; Ingeborg Bachmann; National Socialism; guilt; responsibility; victim; perpetrator; bystander; family; Wir töten Stella; femininity; patriarchy; gendered writing